Política remunerativa y su relación con el desempeño laboral en colaboradores de la Institución Educativa Primaria Secundaria 60188 Simón Bolívar de Iquitos año 2024 - López Solsol, Diana (2025)
The perception of an insufficient and unequal remuneration policy for basic education teachers in Peru negatively affects their job performance in several ways, decreasing teachers' motivation and commitment, leading them to experience burnout and discouragement. This is why the purpose of this research was to identify the relationship between the remuneration policy and job performance in employees of the Primary Secondary Educational Institution 60188 Simón Bolívar of Iquitos in the year 2024, from a quantitative, observational and non-experimental design approach, which identified that there is a positive and significant relationship between the remuneration policy and job performance in employees of the Primary Secondary Educational Institution 60188 Simón Bolívar of Iquitos in the year 2024, which included as a study population the employees of the Primary Secondary Educational Institution 60188 Simón Bolívar of the city of Iquitos amounting to 109. The results show that there is a positive and significant relationship between the remuneration policy and job performance in employees of the Primary Secondary Educational Institution 60188 Simón Bolívar of Iquitos, which suggests that a salary policy A fair and transparent remuneration policy contributes to increased performance, quality of work, proactivity, responsibility and teamwork. Furthermore, employees perceive the remuneration policy as adequate in terms of equity, although areas for improvement in salary competitiveness compared to other similar institutions are identified. The descriptive statistical data highlight that, although the perception of the remuneration policy is mostly favourable, there is room to adjust the salary structure and strengthen the perception of fairness and external competitiveness, in order to optimise staff satisfaction and commitment.